2022
DOI: 10.3746/pnf.2022.27.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Can Anthocyanins Reduce Delayed Onset Muscle Soreness or Are We Barking Up the Wrong Tree?

Abstract: Exercise-induced muscular overload can trigger delayed onset muscle soreness (DOMS). DOMS is related to the indiscriminate use of analgesics and nonsteroidal anti-inflammatory drugs without proper guidance, decreased physical exercise adherence and degenerating sports performance, increased risk of injury, and reduced muscle strength and function. Dietary anthocyanins have been extensively studied as potential natural treatments for DOMS, but the indication, dosage, and form of use remain highly variable. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…This investigation and others have shown that diet-based interventions can influence the oxylipin response to exercise stress without effects on muscle soreness and damage or exercise performance 22 , 23 . Several review papers have concluded that increased intake of blueberries, anthocyanins, and polyphenols in general may have a small, variable, or null effect on mitigating exercise-induced muscle soreness, damage, and dysfunction 29 36 . Changes in muscle damage biomarkers such as creatine kinase and myoglobin following eccentric exercise are highly variable between individuals as confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation and others have shown that diet-based interventions can influence the oxylipin response to exercise stress without effects on muscle soreness and damage or exercise performance 22 , 23 . Several review papers have concluded that increased intake of blueberries, anthocyanins, and polyphenols in general may have a small, variable, or null effect on mitigating exercise-induced muscle soreness, damage, and dysfunction 29 36 . Changes in muscle damage biomarkers such as creatine kinase and myoglobin following eccentric exercise are highly variable between individuals as confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation and others have shown that diet-based interventions can influence the oxylipin response to exercise stress without effects on muscle soreness and damage or exercise performance [22,23]. Several review papers have concluded that increased intake of blueberries, anthocyanins, and polyphenols in general may have a small, variable, or null effect on mitigating exercise-induced muscle soreness, damage, and dysfunction [29][30][31][32][33][34][35][36]. Lipid mediators generated from DHA and EPA have been hypothesized to enhance muscle regeneration by regulating the inflammatory response to muscle injury, but definitive evidence in exercise-based studies is lacking [20,37,38].…”
Section: Discussionmentioning
confidence: 83%
“…The DOMS/EIMD phenomenon may lead to signs and symptoms which range from mild and negligible to severe pain and discomfort and impaired muscle performance capacities in elite and competitive sports [9], but may also be responsible for postural dysfunctions [10]. There are numerous approaches to both prevent and treat DOMS including non-steroidal, anti-inflammatory drugs (NSAIDs) [6,9], as well as dietary [11,12], complementary and alternative medicines (including herbs) [13,14], or physiotherapy (PT) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The DOMS/EIMD phenomenon may lead to signs and symptoms which range from mild and negligible to severe pain and discomfort and impaired muscle performance capacities in elite and competitive sports [9], but may also be responsible for postural dysfunctions [10]. There are numerous approaches to both prevent and treat DOMS including non-steroidal, anti-inflammatory drugs (NSAIDs) [6,9], as well as dietary [11,12], complementary and alternative medicines (including herbs) [13,14], or physiotherapy (PT) [15]. With regards to the latter, those typically include (manual) massage, lymphatic drainage, heat or cold therapy (cryotherapy, ice/cooling, extreme cold), stretching, vibration, lowlevel laser therapy, low-intensity exercise, compression therapy, flossing, or taping, among others.…”
Section: Introductionmentioning
confidence: 99%